Media and politics in Japan - Pharr, S.J Susan. J. Pharr; Pharr, S. J. Susan J.Pharr; Krauss, Ellis S. Ellis S.Krauss (Honolulu : University of Hawai'i Press, 1996)
Japan is one of the most media-saturated societies in the world. The circulations of its "big five" national newspapers dwarf those of any major American newspaper. Its public service broadcasting agency, NHK, is second only to the BBC in size. And it has a full range of commercial television stations, high-brow and low-brow magazines, and a large anti-mainstream media and mini-media.
Includes bibliographical references and index.
Keywords: Mass media -- Political aspects -- Japan; Japan -- Politics and government -- 1945-